Bioinformatics for beginners : genes, genomes, molecular evolution, databases and analytical tools - Choudhuri, Supratim (London : Academic Press, 2014)
Bioinformatics for Beginners provides a coherent and friendly treatment of bioinformatics for any student or scientist within biology who has not routinely performed bioinformatic analysis. The book discusses relevant principles needed to understand the theoretical underpinnings of bioinformatic analysis, and demonstrates with examples targeted analysis using freely available web-based software and publicly available databases. Eschewing non-essential information, the work focuses on principles and hands-on analysis and points to many further study options.
2.3 Molecular Basis of Heritable Genetic Variations-The Raw Materials for Evolution2.3.1 Molecular Basis of Mutation; 2.3.2 Recombination and Generation of Genetic Diversity; 2.3.3 Gene Flow and Introduction of Genetic Diversity; 2.3.4 Origin of New Genes, Creation of Genetic Diversity and Genome Evolution; 2.3.4.1 Origin of New Genes from Coding Sequences (Pre-existing Genes); 2.3.4.1.a Gene Duplication and the 2R Hypothesis; 2.3.4.1.b Exon Shuffling; 2.3.4.1.c Gene Fusion and Fission; 2.3.4.1.d Horizontal Gene Transfer; 2.3.4.2 Origin (de Novo) of New Genes from Noncoding Sequences.
Includes bibliographical references and index.
PDF (ScienceDirect, viewed on July 18, 2014).
Keywords: Bioinformatics; NATURE -- Reference; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- General; Bioinformatics; Bioinformatik; Computational Biology; Electronic books